PENINGKATAN PENGETAHUAN SEBAGAI UPAYA PENCEGAHAN STUNTING DI DUKUH MEDELAN, KECAMATAN SUMBERAGUNG - Nurjanah, Miftah; Nurjanah, Baiti; Reza, Fahmi; Febriyanti, Isna; Zahra , Afifah Aulia; Rahmawati, Nisa; Ulya, Rahmatika; Desnaya, Salma; Agustin, Tia Nanda; Pratiwi, Widia; Leswara, Dianita Febrina (The Journal of Innovation in Community Empowerment, 2025)
Stunting is a condition of growth failure in children caused by inadequate nutritional intake, recurrent infections, and lack of psychosocial stimulation. This problem remains a major public health issue in various regions of Indonesia, including Padukuhan Medelan, Sumberagung District. Based on preliminary observations, the community in this area still has a low level of knowledge regarding the causes and prevention of stunting. This indicates a gap between the community’s need for information and their understanding of stunting. This community service activity aimed to improve public knowledge related to stunting and its prevention efforts. The educational activity on stunting prevention in Padukuhan Medelan was attended by local residents. The implementation method used an interactive lecture approach, which included the delivery of materials on definitions, causative factors, impacts, and stunting prevention strategies, accompanied by a discussion session to deepen participants’ understanding. The results showed an increase in participants’ knowledge about stunting, as evidenced by their active participation during the activity and the achievement of all planned material targets. Overall, the program was well implemented and effective. It is recommended that this program be continued periodically by involving health workers and local government officials to strengthen stunting prevention efforts at the community level